Optimizing Electronic Media for Islamic Studies Teaching and Learning in Nigeria - Yakub, Abdul Waheed Olarewaju; Issah, Jimoh Atolagbe (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2025)
This study examines the pivotal role of electronic media in enriching the teaching and learning of Islamic studies in Nigeria. Despite the growing importance of Islamic education, the adoption of electronic media in Islamic schools remains limited. This research investigates the role of electronic media in Islamic education in Nigeria, highlighting challenges, opportunities, and integration strategies. Utilizing a comprehensive review of literature and empirical data, a questionnaire was administered to a sample of 120 Islamic studies teachers in Nigerian schools, selected through purposive random sampling. The findings highlight the potential of multimedia to enhance learning environments, encourage critical thinking, and overcome traditional educational barriers. The study emphasizes the need for improved teacher training and infrastructure to successfully adopt digital learning tools. It contributes to the existing literature by providing insights into the context-specific challenges and opportunities of integrating electronic media in Islamic education. The findings have implications for policymakers, educators, and researchers seeking to enhance the quality of Islamic education in Nigeria.